VIRAL HEPATITIS B, PREVALENCE, DIAGNOSIS, CLINICAL SIGNIFICANCE OF QUANTITATIVE DETERMINATION OF HBsAg AND ITS CORRELATION WITH GENOTYPES AND VARIANTS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Viral hepatitis B (HBV) is a viral anthroponotic infectious disease with a hemocontact mechanism of transmission. The disease is characterized by cyclical hepatitis, accompanied in some cases by jaundice and possible chronicity. The prevalence of hepatitis B virus (HBV) infection in the world is very high. According to the World Health Organization (WHO) in 2022, almost every third person in the world is infected with the hepatitis B virus, and 254 million people are affected by this chronic infection.